2022
DOI: 10.3389/fphar.2022.843412
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles: Emerging Roles in Developing Therapeutic Approach and Delivery Tool of Chinese Herbal Medicine for the Treatment of Depressive Disorder

Abstract: Extracellular vesicles (EVs) are lipid bilayer-delimited particles released by cells, which play an essential role in intercellular communication by delivering cellular components including DNA, RNA, lipids, metabolites, cytoplasm, and cell surface proteins into recipient cells. EVs play a vital role in the pathogenesis of depression by transporting miRNA and effector molecules such as BDNF, IL34. Considering that some herbal therapies exhibit antidepressant effects, EVs might be a practical delivery approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 157 publications
0
4
0
Order By: Relevance
“…Studies have found that circDYM EVs significantly inhibit microglial activation, BBB leakage and peripheral immune cell infiltration and alleviate the dysfunction of astrocytes induced by CUS ( 108 ). Moreover, EVs may also mediate the treatment of depression and other CNS diseases through Chinese herbal medicine ( 109 ). Researchers obtained EVs secreted by NK cells through the in vitro culture of NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that circDYM EVs significantly inhibit microglial activation, BBB leakage and peripheral immune cell infiltration and alleviate the dysfunction of astrocytes induced by CUS ( 108 ). Moreover, EVs may also mediate the treatment of depression and other CNS diseases through Chinese herbal medicine ( 109 ). Researchers obtained EVs secreted by NK cells through the in vitro culture of NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all cells produce exosomes for varying purposes. Typically, exosomes are highly enriched in a collection of proteins, lipids, and inhibitory nucleic acids ( 82 ), however, expression of tetraspanins, such as CD9, CD63, CD81, CD82 is prototypic for all kinds of exosome vesicles (EVs). Otherwise is the content dependent on the EV-releasing cell type.…”
Section: Exosomes Derived From Tumors and Tregs Contain Cd73mentioning
confidence: 99%
“…Extracellular vesicles (EVs), which are nano- to micro-sized lipid bilayer membrane particles secreted by host cells, play critical roles in novel intercellular communication mechanisms, mediating the transduction of functional molecules with physiological activity, such as microRNAs, mRNAs, proteins, and lipids ( Figure 1 ) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ,…”
Section: Introductionmentioning
confidence: 99%